Implementations for Remotely Preparing Single- and Two-Particle States in a Four-Level System (Journal of Atomic and Molecular Sciences, 2018)
We propose two schemes to realize remote state preparation (RSP). The firstscheme is designed to prepare an arbitrary single-particle state in a four-level system withthe aid of one bipartite maximally entangled channel, which is then generalized to thesecond scheme, i.e., RSP for a two-particle state in a four-level system. During the twopreparations, one single-particle projective measurement and one two-particle projectivemeasurement are performed respectively. Our results show that the preparation for single-particle or two-particle states can be remotely realized with at least 25% successful probability and unit fidelity. Furthermore, with respect to two special ensembles of the preparedstates, i.e., real and equatorial-like, the successful probability can be pushed up to 100%.Hence our probabilistic schemes become deterministic ones.